AN OPTIMAL CONTROL ANALYSIS OF LYMPHATIC FILARIASIS DISEASE TRANSMISSION WITH MASS Diethylcarbamazine (DEC) TREATMENT - MUHAMAD FUADY (NIM: 20111043); Pembimbing: Prof.Dr. Edy Soewono, ANGGA
Lymphatic Filariasis (LF) is an infectious disease that may cause permanent disability to the infected human. This disease caused by nematode worm called malariae and transmitted by mosquitoes. Diethylcarbamazine (DEC) mass treatment is used to suppress the spread of LF. It is assumed that Diethylcarbamazine (DEC) treatment reduces micromalariae and increases the performance of the immune system. Here in this thesis, an optimal control model for Diethylcarbamazine (DEC) mass treatment is discussed. The model represented in a 10-dimensional host-vector system. The host population divided into seven compartments separating the treated and untreated individuals with different infection stages. The vector population is divided into susceptible, window and infected compartments. The basic reproductive ratio of the system which is obtained from the next generation matrix and the analysis of stability of both disease free equlibrium and endemic equilibrium with constant control are shown. Numerical result for optimal control are shown for the case of endemic and outbreak reduction strategies.